Composite multi-quantum well active layer, high light efficiency LED epitaxial wafer and preparation method thereof

CN116705933BActive Publication Date: 2026-10-27JIANGXI ZHAO CHI SEMICON CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310762010.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2026-10-27
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

[0005]基于此,本发明的目的是提供一种复合多量子阱有源层、高光效LED外延片及其制备方法,用于解决现有技术中发光二极管的发光效率低的技术问题

Benefits of technology

[0028]上述复合多量子阱有源层、高光效LED外延片及其制备方法,通过设置复合有源区以及末阱有源区形成复合多量子阱有源层,增加电子和空穴在有源区的复合浓度和效率,有效提升了发光二极管的光效;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116705933B_ABST
    Figure CN116705933B_ABST
Patent Text Reader

Abstract

The application provides a composite multi-quantum well active layer, a high-luminous-efficiency LED epitaxial wafer and a preparation method thereof, and relates to the technical field of semiconductors. The composite multi-quantum well active layer comprises a composite active region and a final well active region arranged on the composite active region. The composite active region comprises a plurality of active regions. The active region comprises a quantum well layer, a cap layer and a quantum barrier layer which are arranged in a periodic and stacked manner. The final well active region comprises a final quantum well layer, a final cap layer and a final quantum barrier layer which are arranged in sequence. The final quantum well layer is arranged above the composite active region. The composite multi-quantum well active layer is formed by arranging the composite active region and the final well active region, the composite concentration and efficiency of electrons and holes in the active region are increased, and the luminous efficiency of the light-emitting diode is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor technology, and in particular to a composite multi-quantum-well active layer, a high-efficiency LED epitaxial wafer, and a method for preparing the same. Background Technology

[0002] With the advancement of epitaxial chip technology and the upgrading of equipment, GaN-based light-emitting diodes can now be applied to fields such as display, lighting, and medical applications, and are continuously developing towards higher luminous efficiency, miniaturization, and integration, attracting widespread attention from researchers.

[0003] The multi-quantum-well active region, as the core region of the LED epitaxial structure, has also been a key area of ​​research. The multi-quantum-well active region of GaN-based light-emitting diodes (LEDs) is generally a periodic structure obtained by alternating growth of low-temperature InGaN quantum wells and high-temperature GaN quantum barrier layers. Because the growth temperature of the quantum barrier GaN layer is relatively high (800℃~900℃), it can damage the previously grown low-temperature (700℃~750℃) InGaN quantum well layer, causing In segregation loss. The common practice is to grow a low-temperature GaN layer as a protective layer before the quantum barrier layer; this protective layer is also called the cap layer. However, the lower temperature can lead to insufficient decomposition of the nitrogen source (NH3) during the growth of the cap layer, resulting in defects such as N vacancies. Therefore, it can also cause In segregation, resulting in an unclear well-barrier interface and thus reducing the luminous efficiency of the LED. Furthermore, in GaN-based light-emitting diodes, because electrons have a smaller effective mass and a higher migration rate than holes, the electron concentration injected into the multi-quantum-well active region is much greater than the hole concentration. This results in the quantum wells that can actually emit light being mainly concentrated in the last few wells near the P-type semiconductor layer, especially at high current densities. A common approach is to use high-barrier AlGaN to block electron overflow, but this method also obstructs hole injection, causing the forward operating voltage to rise.

[0004] In existing technologies, the commonly used low-temperature GaN cap layer in the active region of the quantum well results in insufficient decomposition of the nitrogen source due to the low temperature, leading to defects such as N vacancies that propagate into the well-barrier region, causing blurring of the well-barrier interface and reducing the luminous efficiency of the light-emitting diode. Furthermore, while using a high-barrier AlGaN electron blocking layer structure can hinder electron overflow in the quantum well active region, it also suppresses hole injection, reducing electron-hole recombination efficiency and increasing the operating voltage of the light-emitting diode. Summary of the Invention

[0005] Based on this, the purpose of this invention is to provide a composite multi-quantum-well active layer, a high-efficiency LED epitaxial wafer, and a method for preparing the same, in order to solve the technical problem of low luminous efficiency of light-emitting diodes in the prior art.

[0006] This invention provides a composite multi-quantum-well active layer, comprising a composite active region and a terminal well active region disposed on the composite active region. The composite active region includes multiple active regions, each active region comprising a quantum well layer, a cap layer, and a quantum barrier layer periodically stacked thereon. The quantum well layer includes a quantum well InGaN layer, and the cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature Al layer sequentially disposed on the quantum well layer. x Ga 1-x N-layer, wherein the quantum barrier layer includes a Si-doped high-temperature GaN layer;

[0007] The terminal quantum well active region includes a terminal quantum well layer, a terminal cap layer, and a terminal quantum barrier layer arranged sequentially. The terminal quantum well layer is disposed above the composite active region. The terminal quantum well layer includes a terminal quantum well InGaN layer. The terminal cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature GaN layer arranged sequentially on the terminal quantum well layer. The terminal quantum barrier layer includes a Mg-doped high-temperature GaN layer.

[0008] In addition, the composite multi-quantum-well active layer according to the present invention may also have the following additional technical features:

[0009] Furthermore, the multiple active regions include a front-well active region, a middle-well active region, and a rear-well active region stacked sequentially. In the front-well active region, the number of periods of the quantum well layer, the cap layer, and the quantum barrier layer is 2 to 4; the thickness of the quantum well InGaN layer is 2 nm to 3.5 nm; the thickness of the low-temperature GaN layer is 0.3 nm to 0.5 nm; and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.15 to 0.3. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 3 × 10⁻⁶. 16 cm -3 ~6×10 17 cm -3 .

[0010] Furthermore, in the aforementioned active region with a medium well, the quantum well layer, cap layer, and quantum barrier layer have a period number of 2–4, the thickness of the quantum well InGaN layer is 2 nm–3.5 nm, the thickness of the low-temperature GaN layer is 0.3 nm–0.5 nm, and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.2 to 0.35. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 2 × 10⁻⁶. 16 cm -3 ~4×10 17 cm -3 .

[0011] Furthermore, in the back-well active region, the number of periods for the quantum well layer, the cap layer, and the quantum barrier layer is 1–3; the thickness of the quantum well InGaN layer is 2 nm–3.5 nm; the thickness of the low-temperature GaN layer is 0.3 nm–0.5 nm; and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.1 to 0.2. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 1 × 10⁻⁶. 16 cm -3 ~3×10 17 cm -3 .

[0012] Furthermore, in the front-well active region, the middle-well active region, and the rear-well active region, the Si doping concentration of the quantum barrier layer decreases sequentially.

[0013] Furthermore, in the rear well active region, the front well active region, and the middle well active region, the Al doping concentration of the cap layer increases sequentially.

[0014] Furthermore, the thickness of the final quantum well InGaN layer is 2 nm to 3.5 nm, the thickness of the final cap layer is 0.5 nm to 0.8 nm, the thickness of the Mg-doped high-temperature GaN layer is 10 nm to 18 nm, and the Mg doping concentration is 3 × 10⁻⁶. 17 cm -3 ~1×10 18 cm -3 .

[0015] In one aspect, the present invention also provides a high-efficiency LED epitaxial wafer, comprising a substrate, and a buffer layer, an intrinsic GaN layer, an N-type semiconductor epitaxial layer, a stress relief layer, a composite multi-quantum well active layer, an electron blocking layer, and a P-type semiconductor epitaxial layer sequentially stacked on the substrate, wherein the composite multi-quantum well active layer is the aforementioned composite multi-quantum well active layer.

[0016] Another aspect of the present invention provides a method for preparing a high-efficiency LED epitaxial wafer, which is used to prepare the above-mentioned high-efficiency LED epitaxial wafer, comprising:

[0017] Obtain a substrate;

[0018] A buffer layer, an intrinsic GaN layer, an N-type semiconductor epitaxial layer, a stress relief layer, a composite multi-quantum-well active layer, an electron blocking layer, and a P-type semiconductor epitaxial layer are sequentially grown on the substrate.

[0019] The growth method of the composite multi-quantum-well active layer includes:

[0020] A composite active region and a terminal well active region are sequentially grown on the stress relief layer to form the composite multi-quantum well active layer;

[0021] The method for growing the composite active region includes:

[0022] Multiple quantum well layers, cap layers, and quantum barrier layers are periodically and sequentially grown on the stress relief layer to form the composite active region. The quantum well layer includes a quantum well InGaN layer, and the cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature Al layer sequentially disposed on the quantum well layer. x Ga 1-x The N-layer, the quantum barrier layer comprising a Si-doped high-temperature GaN layer.

[0023] In addition, the high-efficiency LED epitaxial wafer fabrication method of the present invention may also have the following additional technical features:

[0024] Furthermore, in the step of periodically and sequentially growing multiple quantum well layers, cap layers, and quantum barrier layers on the stress relief layer to form the composite active region:

[0025] The growth temperature of the quantum well InGaN layer is 700℃~800℃, and the growth pressure is 100 torr~150 torr;

[0026] The growth temperature of the low-temperature GaN layer is 720℃~740℃, and the growth temperature of the medium-temperature baking layer is 730℃~750℃. The medium-temperature Al x Ga 1-x The growth temperature of the N layer is 750℃~780℃;

[0027] The growth temperature of the Si-doped high-temperature GaN layer is 850℃~900℃.

[0028] The aforementioned composite multi-quantum-well active layer, high-efficiency LED epitaxial wafer, and their fabrication method form a composite multi-quantum-well active layer by setting up a composite active region and a terminal well active region, thereby increasing the recombination concentration and efficiency of electrons and holes in the active region and effectively improving the luminous efficiency of the light-emitting diode.

[0029] Specifically, the composite active region includes multiple active regions, each of which includes a quantum well layer, a cap layer, and a quantum barrier layer stacked periodically in sequence. The cap layer comprises a low-temperature GaN layer, a medium-temperature baked layer, and a medium-temperature Al layer. x Ga 1-x The N-layer, firstly, is essentially a growth pause layer, used to clean the residual In in the cavity, which improves the crystal quality of the well-barrier interface of the composite multi-quantum-well active layer and enhances the antistatic capability of the corresponding light-emitting diode; secondly, the secondary covering medium-temperature Al... x Ga1-x The combination of the N-layer and the low-temperature GaN layer not only protects the In composition in the quantum well but also forms a high conduction band barrier, which blocks electrons flowing through the quantum well. Moreover, its relatively thinness reduces the confinement of holes, thus greatly increasing the recombination probability of holes and electrons in the well. Furthermore, the quantum barrier layer includes a Si-doped high-temperature GaN layer, providing a channel for electron injection and reducing the operating voltage. To avoid excessive Si doping causing the valence band to bend downwards and increasing the height of the hole blocking barrier, a technique of gradient Si doping and Mg doping at the end of the quantum barrier is used to adjust the distribution of charge carriers in the multi-quantum-well region, which can effectively improve the hole injection efficiency in the quantum well, thereby improving the luminous efficiency of the light-emitting diode. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the structure of the high-efficiency LED epitaxial wafer in an embodiment of the present invention;

[0031] Figure 2 This is a schematic diagram of the structure of the composite multi-quantum-well active layer in an embodiment of the present invention;

[0032] Figure 3 This is a schematic diagram of the cap layer structure in an embodiment of the present invention;

[0033] Explanation of main structural symbols:

[0034]

[0035]

[0036] The following detailed description, in conjunction with the accompanying drawings, will further illustrate the present invention. Detailed Implementation

[0037] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Several embodiments of the invention are illustrated in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete.

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0039] To address the low luminous efficiency of light-emitting diodes (LEDs) in existing technologies, this application provides a composite multi-quantum-well active layer, a high-efficiency LED epitaxial wafer, and a method for fabricating the same. By establishing a composite active region and a terminal-well active region to form a composite multi-quantum-well active layer, the recombination concentration and efficiency of electrons and holes in the active region are increased, effectively improving the luminous efficiency of the LED. Specifically, the composite quantum-well active layer structure proposed in this application is essentially a special cap layer design and quantum barrier doping design. Electrons are progressively slowed down in the active region, while the injection concentration and efficiency of holes are increased by using quantum barrier gradient doping and Mg doping in the terminal quantum barrier layer. Therefore, this invention can increase the recombination concentration and efficiency of electrons and holes in the active region, effectively improving the luminous efficiency of the LED, reducing the operating voltage, and enhancing the LED's anti-static capability.

[0040] Specifically, the composite multi-quantum-well active layer provided in this application includes a composite active region 610 and a terminal-well active region 620 disposed on the composite active region. The composite active region includes multiple active regions, each of which includes a quantum well layer 611, a cap layer 612, and a quantum barrier layer 613 periodically stacked in sequence. The quantum well layer includes a quantum well InGaN layer, and the cap layer 612 includes a low-temperature GaN layer 6121, a medium-temperature baking layer 6122, and a medium-temperature Al layer sequentially disposed on the quantum well layer. x Ga 1-x The N-layer 6123 includes a quantum barrier layer comprising a Si-doped high-temperature GaN layer; the terminal well active region 620 includes a terminal quantum well layer 621, a terminal cap layer 622, and a terminal quantum barrier layer 623 arranged sequentially. The terminal quantum well layer is located above the composite active region and includes a terminal quantum well InGaN layer. The terminal cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature GaN layer arranged sequentially on the terminal quantum well layer. The terminal quantum barrier layer includes a Mg-doped high-temperature GaN layer.

[0041] In some alternative embodiments, the multiple active regions include a front-well active region, a middle-well active region, and a back-well active region stacked sequentially, wherein the Si doping concentration of the quantum barrier layer decreases sequentially in the front-well active region, the middle-well active region, and the back-well active region. The Al doping concentration of the cap layer increases sequentially in the back-well active region, the front-well active region, and the middle-well active region.

[0042] Specifically, in the front-well active region, the number of periods for the quantum well layer, cap layer, and quantum barrier layer is 2–4; the thickness of the quantum well InGaN layer is 2 nm–3.5 nm; the thickness of the low-temperature GaN layer is 0.3 nm–0.5 nm; and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.15 to 0.3. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 3 × 10⁻⁶.16 cm -3 ~6×10 17 cm -3 ;

[0043] In the mid-well active region, the period number of the quantum well layer, cap layer, and quantum barrier layer is 2–4, the thickness of the quantum well InGaN layer is 2 nm–3.5 nm, the thickness of the low-temperature GaN layer is 0.3 nm–0.5 nm, and the thickness of the mid-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.2 to 0.35. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 2 × 10⁻⁶. 16 cm -3 ~4×10 17 cm -3 ;

[0044] In the back-well active region, the period number of the quantum well layer, cap layer, and quantum barrier layer is 1–3; the thickness of the quantum well InGaN layer is 2 nm–3.5 nm; the thickness of the low-temperature GaN layer is 0.3 nm–0.5 nm; and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.1 to 0.2. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 1 × 10⁻⁶. 16 cm -3 ~3×10 17 cm -3 .

[0045] Furthermore, the thickness of the final quantum well InGaN layer is 2 nm to 3.5 nm, the thickness of the final cap layer is 0.5 nm to 0.8 nm, the thickness of the Mg-doped high-temperature GaN layer is 10 nm to 18 nm, and the Mg doping concentration is 3 × 10⁻⁶. 17 cm -3 ~1×10 18 cm -3 .

[0046] Another aspect of this application provides a high-efficiency LED epitaxial wafer, including a substrate 10, and a buffer layer 20, an intrinsic GaN layer 30, an N-type semiconductor epitaxial layer 40, a stress relief layer 50, a composite multi-quantum well active layer 60, an electron blocking layer 70, and a P-type semiconductor epitaxial layer 80 sequentially stacked on the substrate, wherein the composite multi-quantum well active layer adopts the aforementioned composite multi-quantum well active layer.

[0047] This application also provides a method for preparing a high-efficiency LED epitaxial wafer, which is used to prepare the above-mentioned high-efficiency LED epitaxial wafer. The preparation method includes steps S11-S12:

[0048] S11. Obtain a substrate.

[0049] In this embodiment, a patterned sapphire substrate is used. Epitaxial growth is performed using an AMEC A7 MOCVD (Metal Organic Chemical Vapor Deposition) system. High-purity N2 (nitrogen) or a mixture of high-purity H2 (hydrogen) and high-purity N2 (nitrogen) is used as the carrier gas, high-purity NH3 as the N source, TMGa (trimethylgallium) and TEGa (triethylgallium) as the Ga source, SiH4 (silane) as the dopant, TMIn (trimethylindium) as the In source, TMAl (trimethylaluminum) as the Al source, and CP2Mg (magnesium pyrocene) as the P-type dopant.

[0050] S12. A buffer layer, an intrinsic GaN layer, an N-type semiconductor epitaxial layer, a stress relief layer, a composite multi-quantum-well active layer, an electron blocking layer, and a P-type semiconductor epitaxial layer are sequentially grown on the substrate.

[0051] Specifically, step S12 includes steps S121-S127:

[0052] S121. Grow a buffer layer on the substrate.

[0053] In a PVD (Physical Vapor Deposition) system, Ar was used as the sputtering gas, N2 was introduced as the precursor, and an Al target was used as the target material. A very small amount of O2 was introduced to adjust the crystal quality, and the temperature was controlled at around 600℃ to sputter an AlN buffer layer on the substrate. The thickness of the buffer layer was 20 nm to 80 nm. As a specific example, the thickness of the AlN buffer layer was 25 nm.

[0054] S122. Grow an intrinsic GaN layer on the buffer layer.

[0055] First, the pressure in the reaction chamber is increased to 150 to 300 torr, and the temperature is increased to 1110°C to 1150°C. TMGa is introduced as the Ga source, NH3 as the N source, and N2 and H2 are used as carrier gases. The N2:H2 ratio is controlled to be approximately 5:300. An intrinsic GaN layer is grown on the AlN buffer layer. The total thickness of the intrinsic GaN layer is 0.8 μm to 1.8 μm. As a specific example, an intrinsic GaN layer with a thickness of 1.6 μm is grown.

[0056] S123. An N-type semiconductor epitaxial layer is grown on the intrinsic GaN layer.

[0057] The N-type semiconductor epitaxial layer primarily provides electrons, with Si as the N-type dopant and a Si doping concentration of approximately 5 × 10⁻⁶. 18 cm -3 ~9×1018 cm -3 The temperature of the reaction chamber is controlled at 1120℃~1180℃, the pressure is 200 torr~400 torr, TMGa is used as the Ga source, NH3 is used as the N source, N2 and H2 are used as carrier gases, and SiH4 is used to provide electrons. An N-type semiconductor epitaxial layer is grown on the intrinsic GaN layer. The thickness of the N-type semiconductor epitaxial layer is 1.5μm~2.5μm. As a specific example, an N-type GaN layer with a thickness of 1.7μm is grown.

[0058] S124. A stress-relieving layer is grown on an N-type semiconductor epitaxial layer.

[0059] Optionally, the thickness of the stress relief layer is 80 nm to 200 nm, and the stress relief layer is composed of In with a low In content. y Ga 1-y The periodic structure obtained by overlapping N-layers and Si-doped GaN layers, where the value of y ranges from 0.1 to 0.25, and a single In... y Ga 1-y The thickness of the N-layer is 4 nm, and the thickness of a single Si-doped GaN layer is 9 nm, with a Si doping concentration of 6 × 10⁻⁶. 17 cm -3 ~1×10 18 cm -3 The stress relief layer has 3 to 8 cycles, and in this example, it has 5 cycles. The stress relief layer is mainly used to alleviate the mismatch stress between the underlying GaN and the InGaN in the multi-quantum-well active region.

[0060] First, an InGaN layer in the stress-relief layer is grown. The reaction chamber pressure is controlled at 100 to 200 torr, and the temperature at 750°C to 850°C. NH3 is used as the N source, N2 as the carrier gas, TEGa as the Ga source, and TMIn as the In source. In this example, the InGaN layer thickness is 4 nm. Next, a Si-doped GaN layer in the stress-relief layer is grown. The temperature is raised to 850°C to 900°C, the pressure remains constant, the In source is turned off, and H2 and SiH4 are introduced to provide dopant. The other gases and the MO source remain unchanged. In this embodiment, the Si-doped GaN layer thickness is 8 nm, and the Si doping concentration is 3 × 10⁻⁶. 17 cm -3 ~8×10 17 cm -3 .

[0061] S125. A composite multi-quantum-well active layer is grown on the stress-relief layer.

[0062] The growth method of the composite multi-quantum-well active layer includes: sequentially growing the composite active region and the end-well active region on the stress-relief layer to form the composite multi-quantum-well active layer.

[0063] Specifically: Multiple quantum well layers, cap layers, and quantum barrier layers are periodically and sequentially grown on the stress relief layer to form a composite active region. The quantum well layer includes a quantum well InGaN layer, and the cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature Al layer sequentially disposed on the quantum well layer. x Ga 1-x The N-layer, the quantum barrier layer, includes a Si-doped high-temperature GaN layer. In this embodiment, a quantum well InGaN layer, a low-temperature GaN layer, a medium-temperature baked layer, and a medium-temperature Al layer are grown sequentially in a periodic cycle. x Ga 1-x The N-layer and the Si-doped high-temperature GaN layer form a composite active region with a cycle number of 2 to 4.

[0064] In some optional embodiments, the growth temperature of the quantum well InGaN layer is 700℃~800℃, and the growth pressure is 100 torr~150 torr; the growth temperature of the low-temperature GaN layer is 720℃~740℃, and the growth temperature of the medium-temperature baking layer is 730℃~750℃; the growth temperature of the medium-temperature Al layer is... x Ga 1-x The growth temperature of the N layer is 750℃~780℃; the growth temperature of the Si-doped high-temperature GaN layer is 850℃~900℃.

[0065] In the composite quantum well active layer, the molar ratio of In component in a single quantum well layer is 20% to 40%; the thickness of a single quantum well layer is 2 nm to 6 nm, the thickness of a single quantum well cap layer is 0.5 nm to 1.0 nm, and the thickness of a single quantum barrier layer is 8 nm to 18 nm.

[0066] Taking the pre-well active region as an example, the growth method of each active region in the composite active region is explained as follows:

[0067] Quantum well layer growth: First, a quantum well InGaN layer is grown. The reaction chamber temperature is controlled at 700℃~800℃, the growth pressure is 100torr~150torr, N2 is used as the carrier gas, NH3 is used as the N source, TMIn is used as the In source, and TEGa is used as the Ga source. The thickness of the grown InGaN layer is 3nm.

[0068] Next, the cap layer was grown. The In source was turned off, while the remaining MO sources and carrier gas were left on. The temperature was raised to 720℃~740℃, and a 0.4nm low-temperature GaN layer was grown. Then, NH3 and TEGa were turned off, and the temperature was raised to 730℃~750℃ and baked for 10 seconds to obtain a medium-temperature baked layer. After that, TEGa was turned on again and NH3 was introduced, while TMAl was used as the Al source. The temperature was raised to 750℃~780℃. During this process, the carrier gas N2 was continuously introduced to grow a 0.4nm medium-temperature Al layer. x Ga 1-x N layers;

[0069] Finally, a quantum barrier layer was grown, TMAl was turned off, H2 and N2 were introduced as carrier gases, the temperature was raised to 850℃~900℃, TEGa was still used as Ga source, and SiH4 was introduced as dopant to grow a 14nm Si-doped high-temperature GaN layer.

[0070] The growth methods for the middle and rear active regions are the same as those for the front active region. Furthermore, the number of cyclic growth cycles for the front, middle, and rear active regions are 3, 3, and 2, respectively.

[0071] The growth conditions of the end-well active region are the same as those of the front-well active region, the middle-well active region, and the back-well active region. The difference is that the end cap layer in the end-well active region is not doped with Al, but only with GaN layer. The end quantum barrier layer is not doped with Si, but is gradually doped with Mg, and the Mg concentration increases from low to high. Therefore, the end quantum barrier layer is a Mg-doped high-temperature GaN layer.

[0072] In GaN-based light-emitting diodes, electrons have a smaller effective mass and a higher migration rate than holes. Therefore, the electron concentration injected into the multi-quantum-well active region is much greater than the hole concentration. This leads to uneven carrier distribution in the multiple quantum wells due to the uneven distribution of electrons and holes. To avoid this problem, this application provides a composite multi-quantum-well active layer comprising a front-well active region, a middle-well active region, a rear-well active region, and a final-well active region. Wherein:

[0073] In the front-well active region, as a specific example, when the number of cycle growth periods of the front-well active region is 3, it can be considered that the three quantum well layers in the front-well active region are consistent with the quantum barrier layer. Its appropriately doped Si quantum barrier layer can shield the polarization electric field, enhance the lateral spread of current, and reduce the operating voltage of the device. Furthermore, the low-Al doped structure in its thinner cap layer has little obstruction to electrons, which helps the further diffusion of electrons. The front-well active region is a secondary light-emitting region, and the main light-emitting regions are the two wells behind the front-well active region, namely the middle-well active region and the rear-well active region. The front-well active region is a sacrificial layer and has a weaker light-emitting intensity.

[0074] Secondly, as a specific example, when the number of cycle growth periods for the middle-well active region and the back-well active region are 3 and 2 respectively, the middle-well active region and the back-well active region are equivalent to five quantum well layers and five quantum barrier layers. The middle-well active region and the back-well active region are important components of light emission. Appropriate Si doping can reduce the device operating voltage, but after Si doping, its valence band bends downward, the hole blocking height barrier increases, and the thickness of the quantum barrier is relatively thick, resulting in a decrease in the efficiency of hole injection from the P side. Therefore, by setting up middle-well active regions and back-well active regions and utilizing their gradient Si doping, the hole injection efficiency of the main light-emitting regions, the middle-well active region and the back-well active region, can be guaranteed. In addition, the high Al content in the cap layer of the middle-well active region can block electrons to a certain extent, preventing electrons from rapidly overflowing from the middle-well active region, making the electron distribution in the middle-well and back-well active regions more uniform.

[0075] Furthermore, to compensate for the lack of holes from the P layer, the composite multi-quantum-well active layer also includes a terminal well active region. The cap layer in the terminal well active region is not doped with Al, and the barrier layer is not doped with Si, which facilitates the injection of holes and serves as the main light-emitting region for emission.

[0076] S126. An electron blocking layer is grown on the composite multi-quantum-well active layer.

[0077] The total thickness of the electron blocking layer is 50nm to 200nm. The chamber temperature is controlled at 920℃ to 970℃, the pressure is 120torr to 220torr, N2 is used as the carrier gas, NH3 is used as the N source, TEGa is used as the Ga source, and TMAl is used as the Al source. The single-stage growth time is 8min, resulting in a 60nm AlGaN electron blocking layer.

[0078] S127. Grow a P-type semiconductor epitaxial layer on the electron blocking layer.

[0079] The chamber temperature is controlled at 920℃~1000℃, and the pressure at 150 torr~300 torr. N2 and H2 are used as carrier gases, NH3 is the N source, and TMGa and Cp2Mg are the Ga and Mg sources, respectively. Here, Mg is a P-type dopant. The thickness of the P-type semiconductor epitaxial layer is 80nm~200nm. As a specific example, the thickness of the P-type semiconductor epitaxial layer is 80nm, and its Mg doping concentration is 1×10⁻⁶. 19 cm -3 ~6×10 19 cm -3 .

[0080] To facilitate understanding of the present invention, several embodiments are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that the disclosure of the present invention will be more thorough and complete.

[0081] Example 1

[0082] The composite multi-quantum-well active layer in the first embodiment of the present invention includes: a composite active region and a final-well active region arranged sequentially. The composite active region includes a front-well active region, a middle-well active region, and a rear-well active region arranged in a periodic cycle. Each of the front-well active region, the middle-well active region, and the rear-well active region includes a quantum well layer, a cap layer, and a quantum barrier layer arranged sequentially. The quantum well layer includes a quantum well InGaN layer, and the cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature Al layer arranged sequentially. x Ga 1-x The N-layer and quantum barrier layer include a Si-doped high-temperature GaN layer;

[0083] The terminal active region includes a terminal quantum well layer, a terminal cap layer, and a terminal quantum barrier layer arranged sequentially. The terminal quantum well layer is located above the composite active region. The terminal quantum well layer includes a terminal quantum well InGaN layer. The terminal cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature GaN layer arranged sequentially. The terminal quantum barrier layer includes a Mg-doped high-temperature GaN layer.

[0084] In the front-well active region, middle-well active region, and rear-well active region of this embodiment, the Al in the cap layer x Ga 1-x In the N-layer, the values ​​of x are 0.17, 0.22, and 0.15, respectively, and the Si doping concentration in the quantum barrier layer is 1.0 × 10⁻⁶. 17 cm -3 ~1.3×10 17 cm -3 7.0×10 16 cm -3 ~7.5×10 16 cm -3 6.2×10 16 cm -3 ~6.5×10 16 cm -3 The Mg doping concentration in the quantum barrier layer of the end-well active region is 4.3 × 10⁻⁶. 17 cm -3 ~5.3×10 17 cm -3 .

[0085] Example 2

[0086] The composite multi-quantum well active layer in the second embodiment of the present invention differs from the composite multi-quantum well active layer in the first embodiment in that:

[0087] In this embodiment, x takes values ​​of 0.19, 0.23, and 0.16, respectively, and the Si doping concentration in the quantum barrier layer is 1.2 × 10⁻⁶. 17cm -3 ~1.4×10 17 cm -3 7.3×10 16 cm -3 ~7.7×10 16 cm -3 6.5×10 16 cm -3 ~6.8×10 16 cm -3 The Mg doping concentration in the quantum barrier layer of the end-well active region is 4.8 × 10⁻⁶. 17 cm -3 ~5.8×10 17 cm -3 .

[0088] Example 3

[0089] The composite multi-quantum well active layer in the third embodiment of the present invention differs from the composite multi-quantum well active layer in the first embodiment in that:

[0090] In this embodiment, x takes values ​​of 0.16, 0.21, and 0.13, respectively, and the Si doping concentration in the quantum barrier layer is 8 × 10⁻⁶. 16 cm -3 ~9×10 16 cm -3 7.0×10 16 cm -3 ~7.2×10 16 cm -3 6.5×10 16 cm -3 ~6.8×10 16 cm -3 The Mg doping concentration in the quantum barrier layer of the active region at the end well is 4.1 × 10⁻⁶. 17 cm -3 ~5.1×10 17 cm -3 .

[0091] Comparative Example

[0092] The comparative examples used a conventional constant Si-doped quantum barrier GaN layer and a low-temperature GaN cap layer (loop: 8+1), with the final quantum barrier layer undoped. The Si doping concentrations in the quantum barrier layers of Comparative Examples 1, 2, and 3 were given as 7.2 × 10⁻⁶. 16 cm -3 ~7.6×10 16 cm -3 7.4×10 16 cm -3 ~8.0×10 16 cm-3 6.8×10 16 cm -3 ~7.2×10 16 cm -3 .

[0093] To better illustrate the superior performance of the light-emitting diode (LED) obtained using the composite multi-quantum-well active layer in this embodiment, please refer to Table 1. Table 1 presents performance data of LEDs fabricated using the composite multi-quantum-well active layers of Embodiments 1-3 of this application. These data are based on specific experimental results from various embodiments of the present invention. Table 1 also includes performance data of LEDs fabricated using existing multi-quantum-well active layers, as detailed below:

[0094] Table 1:

[0095] Example 1 98.5 199.8 3.13 Example 2 97.9 199.4 3.14 Example 3 98.2 199.9 3.16 Comparative Example 1 96.2 195.5 3.20 Comparative Example 2 95.8 196.1 3.19 Comparative Example 3 97.1 195.3 3.21

[0096] As shown in Table 1, the light-emitting diodes prepared by the method of the present invention have higher luminous intensity, stronger antistatic capability and lower operating voltage.

[0097] In summary, the composite multi-quantum-well active layer, high-efficiency LED epitaxial wafer, and their fabrication method in the above embodiments of the present invention, by setting a composite active region and a terminal well active region to form a composite multi-quantum-well active layer, increase the recombination concentration and efficiency of electrons and holes in the active region, and effectively improve the luminous efficiency of the light-emitting diode.

[0098] Specifically, the composite active region includes multiple active regions, each of which includes a quantum well layer, a cap layer, and a quantum barrier layer stacked periodically in sequence. The cap layer comprises a low-temperature GaN layer, a medium-temperature baked layer, and a medium-temperature Al layer. x Ga 1-x The N-layer, firstly, is essentially a growth pause layer, used to clean the residual In in the cavity, which improves the crystal quality of the well-barrier interface of the composite multi-quantum-well active layer and enhances the antistatic capability of the corresponding light-emitting diode; secondly, the secondary covering medium-temperature Al... x Ga 1-xThe combination of the N-layer and the low-temperature GaN layer not only protects the In composition in the quantum well but also forms a high conduction band barrier, which blocks electrons flowing through the quantum well. Moreover, its relatively thinness reduces the confinement of holes, thus greatly increasing the recombination probability of holes and electrons in the well. Furthermore, the quantum barrier layer includes a Si-doped high-temperature GaN layer, providing a channel for electron injection and reducing the operating voltage. To avoid excessive Si doping causing the valence band to bend downwards and increasing the height of the hole blocking barrier, a technique of gradient Si doping and Mg doping at the end of the quantum barrier is used to adjust the distribution of charge carriers in the multi-quantum-well region, which can effectively improve the hole injection efficiency in the quantum well, thereby improving the luminous efficiency of the light-emitting diode.

[0099] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0100] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A composite multi-quantum-well active layer, characterized in that, The active region includes a composite active region and a terminal well active region disposed on the composite active region. The composite active region includes multiple active regions, each active region comprising a quantum well layer, a cap layer, and a quantum barrier layer periodically stacked. The quantum well layer includes a quantum well InGaN layer, and the cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature Al layer sequentially disposed on the quantum well layer. x Ga 1-x N-layer, wherein the quantum barrier layer includes a Si-doped high-temperature GaN layer; The terminal quantum well active region includes a terminal quantum well layer, a terminal cap layer, and a terminal quantum barrier layer arranged sequentially. The terminal quantum well layer is disposed above the composite active region. The terminal quantum well layer includes a terminal quantum well InGaN layer. The terminal cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature GaN layer arranged sequentially on the terminal quantum well layer. The terminal quantum barrier layer includes a Mg-doped high-temperature GaN layer.

2. The composite multi-quantum well active layer according to claim 1, characterized in that, Multiple active regions include a front-well active region, a middle-well active region, and a back-well active region stacked sequentially. In the front-well active region, the quantum well layer, the cap layer, and the quantum barrier layer have 2 to 4 periods. The thickness of the quantum well InGaN layer is 2 nm to 3.5 nm, the thickness of the low-temperature GaN layer is 0.3 nm to 0.5 nm, and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.15 to 0.

3. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 3 × 10⁻⁶. 16 cm -3 ~6×10 17 cm -3 .

3. The composite multi-quantum well active layer according to claim 2, characterized in that, In the aforementioned active region with a medium well, the quantum well layer, cap layer, and quantum barrier layer have a period number of 2-4; the thickness of the quantum well InGaN layer is 2nm-3.5nm; the thickness of the low-temperature GaN layer is 0.3nm-0.5nm; and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.2 to 0.

35. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 2 × 10⁻⁶. 16 cm -3 ~4×10 17 cm -3 .

4. The composite multi-quantum well active layer according to claim 2, characterized in that, In the back-well active region, the quantum well layer, cap layer, and quantum barrier layer have a period number of 1 to 3; the thickness of the quantum well InGaN layer is 2 nm to 3.5 nm; the thickness of the low-temperature GaN layer is 0.3 nm to 0.5 nm; and the thickness of the medium-temperature Al... x Ga 1-x The thickness of the N-layer is 0.2 nm to 0.4 nm, and the value of x is 0.1 to 0.

2. The thickness of the Si-doped high-temperature GaN layer is 10 nm to 18 nm, and the Si doping concentration is 1 × 10⁻⁶. 16 cm -3 ~3×10 17 cm -3 .

5. The composite multi-quantum well active layer according to claim 2, characterized in that, In the front-well active region, the middle-well active region, and the rear-well active region, the Si doping concentration of the quantum barrier layer decreases sequentially.

6. The composite multi-quantum well active layer according to claim 2, characterized in that, In the back well active region, the front well active region, and the middle well active region, the Al doping concentration of the cap layer increases sequentially.

7. The composite multi-quantum-well active layer according to claim 1, characterized in that, The thickness of the final quantum well InGaN layer is 2 nm to 3.5 nm, the thickness of the final cap layer is 0.5 nm to 0.8 nm, the thickness of the Mg-doped high-temperature GaN layer is 10 nm to 18 nm, and the Mg doping concentration is 3 × 10⁻⁶. 17 cm -3 ~1×10 18 cm -3 .

8. A high-efficiency LED epitaxial wafer, comprising a substrate, and a buffer layer, an intrinsic GaN layer, an N-type semiconductor epitaxial layer, a stress relief layer, a composite multi-quantum-well active layer, an electron blocking layer, and a P-type semiconductor epitaxial layer sequentially stacked on the substrate, characterized in that, The composite multi-quantum well active layer is the composite multi-quantum well active layer described in any one of claims 1-7.

9. A method for preparing a high-efficiency LED epitaxial wafer, characterized in that, The method for preparing the high-efficiency LED epitaxial wafer of claim 8 includes: Obtain a substrate; A buffer layer, an intrinsic GaN layer, an N-type semiconductor epitaxial layer, a stress relief layer, a composite multi-quantum-well active layer, an electron blocking layer, and a P-type semiconductor epitaxial layer are sequentially grown on the substrate. The growth method of the composite multi-quantum well active layer includes: sequentially growing a composite active region and a terminal well active region on the stress relief layer to form the composite multi-quantum well active layer; The method for growing the composite active region includes: Multiple quantum well layers, cap layers, and quantum barrier layers are periodically and sequentially grown on the stress relief layer to form the composite active region. Each quantum well layer includes a quantum well InGaN layer, and the cap layer includes a low-temperature GaN layer, a medium-temperature baking layer, and a medium-temperature Al layer sequentially disposed on the quantum well layer. x Ga 1-x The N-layer, the quantum barrier layer comprising a Si-doped high-temperature GaN layer.

10. The method for preparing a high-efficiency LED epitaxial wafer according to claim 9, characterized in that, In the step of periodically and sequentially growing multiple quantum well layers, cap layers, and quantum barrier layers on the stress relief layer to form the composite active region: The growth temperature of the quantum well InGaN layer is 700℃~800℃, and the growth pressure is 100 torr~150 torr; The growth temperature of the low-temperature GaN layer is 720℃~740℃, and the growth temperature of the medium-temperature baking layer is 730℃~750℃. The medium-temperature Al x Ga 1-x The growth temperature of the N layer is 750℃~780℃; The growth temperature of the Si-doped high-temperature GaN layer is 850℃~900℃.

Citation Information

Patent Citations

  • Light-emitting diode (LED)

    CN102194968A

  • Light emitting diode and method of fabricating the same

    KR1020130030178A